SOUTHERN BLUEFIN TUNA IN THE INDONESIAN LONGLINE FISHERY: HISTORICAL DEVELOPMENT, SEASON, SOME BIOLOGICAL PARAMETERS; LANDING ESTIMATION AND CATCH STATISTICS FOR 1993 - Tim Davis; Sofri Bahar; Jessica Farley (Indonesian Fisheries Research Journal, 1995)
The longline fishery based in Beli her expended rapidly in rcccnt ycrrs: 291 vcarcls,mdnly of reiwancsc origin, operatcd out of Benor in 1993.